2013
DOI: 10.1007/s12033-013-9712-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reference Genes for Real-Time Quantitative PCR Gene Expression Normalization During C2C12 and H9c2 Skeletal Muscle Differentiation

Abstract: Skeletal muscle differentiation occurs during muscle development and regeneration. To initiate and maintain the differentiated state, a multitude of gene expression changes occur. Accurate assessment of these differentiation-related gene expression changes requires good quality template, but more specifically, appropriate internal controls for normalization. Two cell line-based models used for in vitro analyses of muscle differentiation incorporate mouse C2C12 and rat H9c2 cells. In this study, we set out to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…For the induction of differentiation, H9c2 cells on 2D gelatincoating substrates were first cultured in GM for 24 hr. The medium was then changed to low-serum differentiation medium (DM; DMEM supplemented with 1% FBS) and cultured for 14 days for the differentiation experiments (Masilamani, Loiselle, & Sutherland, 2014). The DM was changed every 2-3 days.…”
Section: H9c2 Myoblast Culture and Seeding Into The Gelatin Bubble-mentioning
confidence: 99%
“…For the induction of differentiation, H9c2 cells on 2D gelatincoating substrates were first cultured in GM for 24 hr. The medium was then changed to low-serum differentiation medium (DM; DMEM supplemented with 1% FBS) and cultured for 14 days for the differentiation experiments (Masilamani, Loiselle, & Sutherland, 2014). The DM was changed every 2-3 days.…”
Section: H9c2 Myoblast Culture and Seeding Into The Gelatin Bubble-mentioning
confidence: 99%
“…Both GAPDH and 18S rRNA were stable and unaffected by MC-LR exposure, similar to the results reported in HepG2 cells (Žegura et al, 2006, 2008) and carp (Jiang et al, 2013), therefore both of them were used as the endogenous assay control. The geometric mean of the expression level of GAPDH and 18S rRNA was used to normalize the RT-qPCR data (Vandesompele et al, 2002;Goossens et al, 2005;Nielsen and Boye, 2005;Masilamani et al, 2014).…”
Section: Gene Namementioning
confidence: 99%
“…Selection of an appropriate set of reference genes under such a varied suite of conditions is thus non-trivial, yet nevertheless critical for accurate measurement of gene expression during myogenesis. A number of studies have identified candidate reference genes for use in studies of mature muscle (and in cultured, terminally-differentiated myotubes) in a range of species8 , 9 , 10 , 11 , 12 , though candidates for normalization of gene expression throughout the myogenic program (particularly in cell culture) are more limited13 , 14, and are generally specific to a single cell line. Furthermore, such studies typically use at most 5 or 6 candidate genes (occasionally as few as 3), and do not necessarily validate the candidates identified against multiple genes with known expression patterns.…”
Section: Introductionmentioning
confidence: 99%